Randomly amplified polymorphic DNA (RAPD)fingerprinting of Schizothorax richardsonii (Gray) - Kapila, Rajeev; Mishra, D P (Indian Journal of Fisheries, 2011)
Randomly amplified polymorphic DNA (RAPD) fingerprinting was used to assessthe genetic variation/similarity among snow trout (Schizothorax richardsonii)collected from four wild locations. RAPD profiles were generated using tenoligonucleotide pimers which produced repeatable and consistent results. Ninetyeight RAPD loci were detected with average of 9.8 bands per primer. Sixty nineof these loci wereÂ polymorphic exhibiting location specific as well as individualspecific bands. Twenty nine of the loci exhibited species specific monomorphism.Dendrograms prepared using unweighted pair group method with arithmeticaverages (UPGMA) using Jaccardâ€™s similarity coefficient revealed fishes fromneighboring locations were more genetically similar than the distant ones.